Iron-based trinuclear metal-organic nanostructures on a surface with local charge accumulation - Cornelius Krull (Nature Portfolio, 2018)
Polynuclear metal-organic coordination complexes are often inaccessible by traditional synthetic chemistry methods. Here, the authors use on-surface supramolecular chemistry to form a planar trinuclear Fe complex, in which an accumulation of electrons around the positive mixed-valence polynuclear centre suggests a catalytically active core.